2020
DOI: 10.1140/epjc/s10052-020-8005-8
|View full text |Cite
|
Sign up to set email alerts
|

Non-singular solution for anisotropic model by gravitational decoupling in the framework of complete geometric deformation (CGD)

Abstract: We presented a non-singular solution of Einstein’s field equations using gravitational decoupling by means of complete geometric deformation (CGD) in the anisotropic domain for compact star models. In this approach both the gravitational potentials are deformed as $$ \nu =\xi +\beta \,h(r)$$ν=ξ+βh(r) and $$ e^{-\lambda }=\mu +\beta \,f(r)$$e-λ=μ+βf(r), where $$\beta $$β is a coupling constant. Then we solve more complex field equations under above transformations by using a particular form of deformation funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 67 publications
0
16
0
Order By: Relevance
“…Due to this, we need only two extra conditions in order to close the system. There are many ways to solve the equation despite the appearance of the new degree of freedom h(r ) in the θ -sector, such as implementing the mimick approach with a particular form of h(r ), or using the EoS approach together with the mimick approach [19][20][21] to solve the -sector. On the other hand, it must be noted that the hydrostatic balance gets severely modified because of the deformation.…”
Section: Introductionmentioning
confidence: 99%
“…Due to this, we need only two extra conditions in order to close the system. There are many ways to solve the equation despite the appearance of the new degree of freedom h(r ) in the θ -sector, such as implementing the mimick approach with a particular form of h(r ), or using the EoS approach together with the mimick approach [19][20][21] to solve the -sector. On the other hand, it must be noted that the hydrostatic balance gets severely modified because of the deformation.…”
Section: Introductionmentioning
confidence: 99%
“…So while working with EGD, it is very important to check the hydrostatic balance to find out the model is acceptable realistically or not. In light of EGD, some recent research work can be found in references [75,76].…”
Section: Introductionmentioning
confidence: 99%
“…The general framework for studying class I spacetimes within the context of the MGD and CGD approaches were provided by Maurya and his collaborators. [ 48–50 ] The MGD in axially symmetric systems and rotating black holes has been applied by Contreras et al. [ 43 ] as well as some other works on dark matter, black holes and Dirac stars in the context of MGD are obtained by the authors.…”
Section: Introductionmentioning
confidence: 99%